Linguistic homogeneity in Galician and Portuguese borderland communities - Beswick, Jaine (Sociolinguistic Studies, 2005)
This paper discusses recent research findings within the borderland regions of southern Galicia and northern Portugal regarding the linguistic continuity and the use of language as a symbol of ethnic identity. A brief historical overview outlines the social, ethnic and cultural borders and their configuration within geographical and political frontiers. The notion of border regimes and synchronic cross-border geolinguistic diffusion is examined to determine the extent of mutual intelligibility, the distribution of contextual functions within the borderland communities and the extent of the dialectal continuum. The opinions of the borderland communities regarding the issue of ethnolinguistic identities, their emblematic and unifying characterisations and impact within cross-border cultures are then examined, taking into consideration the official language status of both Galician and Portuguese within their respective territories. Speculative conclusions indicate that because of increased cross-border contact, phonetic levelling is occurring between the varieties.